Si Surface Orientation Dependence on the Electrical Characteristics of HfN Gate Insulator with sub-0.5 nm EOT Formed by ECR Plasma Sputtering. Issue 1588 (20th February 2014) - Atthi, Nithi; Han, Dae-Hee; Ohmi, Shun-ichiro
ABSTRACT: This paper investigated the silicon substrate orientation dependence on the electrical properties of high-κ HfN gate insulator formed by electron-cyclotron-resonance (ECR) plasma sputtering. The effect of N2 /4.9%H2 forming-gas annealing (FGA) was studied. By using N2 /4.9%H2 FGA at 500°C for 20 min, the interfacial layer (IL) formation was not formed and led to the zero-interface layer (ZIL). The EOTs of 0.47 and 0.51 nm with leakage current of 1.1 and 1.4 A/cm 2 (@VFB -1 V) were obtained on p-Si(100) and p-Si(110), respectively. The density of interface states (Dit ) with the order of 1011 cm -2 eV -1 was obtained on both p-Si(100) and p-Si(110). This suggests that the direct deposition of HfN film with ZIL prevented the degradation of electrical characteristics on the p-Si(100) and p-Si(110) substrate in comparison to the case of oxide-based hafnium gate insulator.